Dual System Curriculum in Chemical Engineering Education - Abdul Halim (International Journal of Chemistry Education Research, 2022)
Higher education for chemical engineering is required to fulfill several aspects of the required skill and knowledge requested by stakeholders, including professional societies, company partners, accreditation boards, and national standards. Ministry of education of Indonesia under Makarim administration also mandated more liberal practice in Indonesian higher education as jargoned as "Merdeka Belajar Kampus Merdeka (MBKM)" means "freedom to learn, freedom campus". These several aspects, combined with the current COVID-19 pandemic, bring a massive problem in the curriculum. Herein, we discuss and propose a dual system curriculum to accommodate the government standard's requirement, minimize the gap between education and industry, and the professional association. The initial implementation in two universities is observed and the challenges, future direction and lesson learned are discussed. We expect the curriculum gives the student experience learning in the classroom and a live laboratory in conjunction with MBKM's spirit.